A Ypt/Rab effector complex containing the Sec1 homolog Vps33p is required for homotypic vacuole fusion - Seals, Darren F. (The National Academy of Sciences, 2000)
Yeast vacuoles undergo priming, docking, and homotypic fusion, although little has been known of the connections between these reactions. Vacuole-associated Vam2p and Vam6p (Vam2/6p) are components of a 65S complex containing SNARE proteins. Upon priming by Sec18p/NSF and ATP, Vam2/6p is released as a 38S subcomplex that binds Ypt7p to initiate docking. We now report that the 38S complex consists of both Vam2/6p and the class C Vps proteins [Reider, S. E. and Emr, S. D. (1997) Mol. Biol. Cell 8, 2307–2327]. This complex includes Vps33p, a member of the Sec1 family of proteins that bind t-SNAREs. We term this 38S complex HOPS, for homotypic fusion and vacuole protein sorting. This unexpected finding explains how Vam2/6p associates with SNAREs and provides a mechanistic link of the class C Vps proteins to Ypt/Rab action. HOPS initially associates with vacuole SNAREs in “cis” and, after release by priming, hops to Ypt7p, activating this Ypt/Rab switch to initiate docking.